Tobacco point of sale advertising increases positive brand user imagery - Donovan, Robert; Jancey, Jonine; Jones, Sandra (BMJ Publishing Group, 2002)
Objectives: To determine the potential impact of point of sale advertising on adolescents so as to inform changes to the Tobacco Control Act. Design: Participants were randomly assigned to one of two conditions. In the control condition, students were exposed to a photograph of a packet of cigarettes; in the intervention condition, students were exposed to an ad for cigarettes, typical of point of sale advertising posters. All students then rated the brand user on a set of 12 bipolar adjectives. Two brands were used in the study: Benson & Hedges, and Marlboro. Subjects: One hundred year (grade) 6 and 7 students (age range 10–12 years), from four Western Australian metropolitan primary schools, participated in the study.Results: In a majority of the brand user descriptions, the cigarette advertisements increased brand user imagery in a positive way, especially for Benson & Hedges. For example, participants viewing the Benson & Hedges advertisement, as distinct from those viewing the Benson & Hedges pack only, were more likely to describe the Benson & Hedges user as relaxed, interesting, cool, rich, adventurous, and classy. Relative to the Marlboro pack only, the Marlboro ad increased positive perceptions of the Marlboro user on adventurous, interesting, and relaxed. Conclusions: The results presented here support restrictions being placed on advertising at point of sale, since such ads have the potential to increase positive brand user imagery directly in the situation where a product purchase can take place, and hence the potential to increase the likelihood of impulse purchasing.